Y-maze performance predicts refined motor learning in mice - Isak Karlsson; Thawann Malfatti; Klas Kullander; Samer Siwani; Barbara Ciralli (PLoS ONE, 2026)
The relationships between distinct abilities and their interdependencies during memory tasks and motor learning activities are not clear. An important question is whether being proficient in memory or motor learning tasks also translates into better performance in another, similar task – reflecting potential generalization of motor learning abilities. To investigate the correlation between memory performance and motor learning, we used a combination of behavioral tasks that assess general exploratory behavior, declarative memory, and fine motor learning in female mice. For the exploratory behavior, we used the open field task, and assessed declarative memory using the novel object recognition and Y-maze. Motor performance and learning was assessed through the vertical pole and pellet reaching tasks. We found a positive correlation between the Y-maze and the pellet reaching task performance, where a higher exploration rate indicated a higher success ratio in the pellet reaching task. Further, leave-one-out cross-validation prediction analysis show that Y-maze performance is a robust predictor of pellet reaching performance, showing that mice pellet reaching performance can reliably be predicted from Y-maze performance. These results can be used to conduct a pre-study for challenging motor tasks that include pre-behavioral procedures on mice. Our study shows that performance in the Y-maze predicts pellet reaching performance, indicating that these tasks can be used as pre-screening for motor learning performance and activity.